Handbook of behavioral economics : foundations and applications. - Bernheim, B. Douglas; Della Vigna, Stefano; Laibson, David I. (Handbooks in economics., 2019)
"Handbook of Behavioral Economics, Volume 2, Foundations and Applications offers critical perspectives on theoretical work within behavioral economics, delivering a comprehensive, critical, up-to-date, and accessible review of the field that has always been missing. This literature summary of the conceptual foundations underlying behavioral economics is written by, and for, economists, with chapters covering Intertemporal choice, Reference-dependent preferences, Beliefs, Cognition, Social preferences, Behavioral game theory, Welfare, and Neuroeconomics. Helps academic and non-academic economists understand recent rapid changes in theoretical advances within behavioral economics Designed for economists already convinced of the benefits of behavioral economics and mainstream economists who feel threatened by new developments in behavioral economics Written for those who wish to become quickly acquainted with behavioral economics."--